Automotive dashboard indicator : consequences of different types of indicator to the driver / Mohd Taufik Zulkefli - Zulkefli, Mohd Taufik (2019)
Automotive dashboard indicator is a way of interaction between cars and drivers. Located on the instrument cluster, it indicates usage of some features or function in a type of symbol or acronym such as handbrake, lamps and also as a warning to the driver a malfunction of some components or current condition of the car. The introduction of new electronic or safety features also contributes to the existence of new indicator on instrument cluster. However, some drivers are not aware of the important usage of this indicator. Drivers who understand a certain indicator are confused when they found a same indicator but presented in different symbol or acronym in some models of cars. This study investigates the possible consequences when some indicators are displayed in different symbols or acronyms. The focus is on a possibility of confusion and distraction while driving. A quantitative method has been used as it can easily gain results based from the questionnaire survey into the numerical data. Regarding to the result of this study, it is found that different types of some indicators raise confusion among drivers and there is a need to standardize these indicators. Therefore, this study will benefit the automotive manufacturers to revise a design of indicators that can be easily recognized and user friendly, hence will raise awareness among drivers the importance of those indicators to assist them while driving